Waste Bank Design Proposal for Kampung Susun Kunir - Sunoto, Asri Ardiati (Jurnal Pengabdian West Science, 2025)
In Kampung Susun Kunir, the volume of waste from residents and surrounding residents combines to form piles that pollute the environment. For this reason, it is necessary to implement 3R (reduce, reuse and recycle) waste. One of the activities that supports this is the establishment of a Waste Bank. Therefore, the author proposes a Waste Bank design in the Kampung Susun Kunir area. Due to limited space, the design of the Waste Bank is made flexible, semi-permanent in the form of a Y-banner indicating the classification of waste types which also shows the location of collection, weighing and recording of related waste.
Keywords: Waste Bank; Kampung Susun Kunir